Mimicking evolution of 'mini-homeostatic' modules in supramolecular systems. (March 2021) - Panja, Santanu; Adams, Dave J.
Abstract: Natural systems maintain steady internal, physical, and chemical conditions (i.e. they exhibit homeostasis) and keep control over their local environment by creating many mini-homeostatic modules. In comparison, synthetic materials are typically formed under equilibrium or kinetically trapped conditions and do not usually change their properties with time. Hence, synthetic systems are typically devoid of self-regulation, self-correction and self-monitoring. Because of their static nature, reconfiguration of synthetic systems is also difficult as they exhibit unidirectional responses to perturbation. Here, we describe a hydrogel-based homeostatic system with self-monitoring and self-regulating properties over a cyclic energy input. Unlike other dynamic gels under feedback loops, our system maintains its gel form throughout the energy cycle across a wide pH range. Control over the evolution of the mini-homeostatic modules induces a self-correcting property to our homeostatic hydrogel which can tune the network type and improve the mechanical properties of the system. Graphical abstract: Image, graphical abstract